2008
DOI: 10.14236/jhi.v16i3.697
|View full text |Cite
|
Sign up to set email alerts
|

Do electronic medical record (EMR) demonstrations change attitudes, knowledge, skills or needs?

Abstract: Introduction Electronic medical records (EMRs) are the future of primary care. Transition to electronic records can have a significant impact on physicians, office staff, nursing staff and patients. There are no published EMR studies combining these four populations or studies that have evaluated the impact of EMR demonstrations. To better understand the impact of EMRs, an online survey was administered before and after EMR demonstrations. Methods A longitudinal cohort survey design was used to assess primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 19 publications
2
25
0
Order By: Relevance
“…Demonstrations of use were helpful; Beiter et al found the same. 38 Prescribers were enthusiastic about the ability to prescribe from home, which may correlate with the proportion of prescribers who indicated that they use a computer at home for professional use, especially the increase seen for SL prescribers, when comparing Phase 2 with Phase 1. This in turn was associated with scores on the four domains.…”
Section: Box 1 What This Paper Addsmentioning
confidence: 99%
“…Demonstrations of use were helpful; Beiter et al found the same. 38 Prescribers were enthusiastic about the ability to prescribe from home, which may correlate with the proportion of prescribers who indicated that they use a computer at home for professional use, especially the increase seen for SL prescribers, when comparing Phase 2 with Phase 1. This in turn was associated with scores on the four domains.…”
Section: Box 1 What This Paper Addsmentioning
confidence: 99%
“…8 It is known that clinicians' attitude towards EHR depends on many factors including computer literacy, 9 cost and interoperability, 5 public opinion, 10 privacy concerns, 5,10,11,12 reliability, 13 and the will to share among the clinical teams 12 and with the patients, 14 but there is no guideline or policy on what should be shared and what type of code should populate the Problem List. Implementation and use of EHR is affected positively by demonstration of the EHR 15 and access to simulations. 16 Perhaps more important is the fact that, even if there are initial barriers to EHRs, they are used successfully by all clinicians 17 despite concerns about the interference with the process of the consultation 18,19 or its effect on decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Diabetes registration systems can be effective in organising patient education and communication, for patients to receive online information and for generating reminders. 34 Impact on processes of care and clinical outcomes Diabetes registers and EMRs used for tracking diabetes patients are implicitly and explicitly promoted as effective and necessary management tools with the potential for improving diabetes care. 35,36 The extent to which this information system is developed, updated and integrated by health professionals into the process of care for diabetes patients depends on whether they believe that a diabetes register will impact on patient quality of care and outcomes.…”
Section: Discussionmentioning
confidence: 99%